ANALYSIS OF MEDICAL UNIVERSITY STUDENTS' OPINIONS ON TEAMWORK AND TEAM INTERACTION - Anna V. Belyaeva; Marina G. Yanova; Aleksey Yu. Senchenko; Galina V. Senchenko (Russian Journal of Education and Psychology)
Background. The need to develop team skills in medical students is due to their importance for the successful performance of professional duties. However, despite the high importance of teamwork, modern students are not sufficiently prepared for team interaction.